Role and development of personal husbandries in solving employment issues in the region - Shinet, G.G.; Zhadigerova, G.A.; Yesbolova, A.Y.; Andarova, R.K.; Zhussipova, E.E. (BUKETOV BUSINESS REVIEW, 2020)
Object: The content of the article is intended for agriculture to contribute to the solution of a social problem – employment of the population. Methods: It provides for the functioning of the population’s economy in the agriculture of the Republic of Kazakhstan and its share in the production of agricultural products today. It describes the principle of operation, quantitative indicators of population farms, the share in the production of agricultural products. Quotes about the conduct of numerous studies on the self-employment of the agricultural population. Results: Farms of the population explained the current situation in agriculture, which has its own share in the employment of the rural population. However, there are no complete targeted comprehensive studies for the study of rural employment. In this regard, the validity of the study and analysis of this topic is given. By providing quantitative data, the public has proved that agriculture has a significant share in the production of agricultural products. Conclusions: This covered the employment of the rural population, which in the competition can be found in the interpretation of their income. This explains that rural populaton isself-employed and earns on household farms.